Experimental investigation on thermodynamic properties and crystal structure of La0.78Ba0.22MnO3 compounds - Hashimov, R. F.; Mikailzade, F. A.; Trukhanov, S., V; Trukhanov, A., V; Mirzayeva, D. M. (World Scientific Publ Co Pte Ltd, 2020)
In this work, powder (La(0.7)8Ba(0.22)MnO(3)) samples (purity of 99.99 % and density of 2.6 g/cm(3)) were used. The crystal structure of La0.63Ba0.37MnO3 compound was studied by X-ray diffraction method. It was determined that the crystal structure of this compound consists of two phases at room-temperature and under normal condition. These structure phases correspond to the cubic symmetry with Pm-3m space group and rhombohedral symmetry with the R-3c space group. Thermo Gravimetric (TG), Differential Scanning Calorimetry (DSC), Differential Thermo Gravimetric (DTG) and Differential Thermal Analysis (DTA) of La0.63Ba0.37MnO3 compound were carried out in a hightemperature range of 30 <= T <= 890 degrees C. It has been found that at high-temperatures, two-phase transition occurs in this compound. The value of thermodynamic parameters was found out for each phase transit.
Keywords: Magnetic materials; crystal structure; different temperatures; phase transition; thermal mechanism